Efektifitas Tindakan Keperawatan Dalam Pemberian Nutrisi Enteral Antara Metode Intermittent Feeding Terhadap Pasien Di Ruangan Icu Rumah Sakit Makassar Sulawesi Selatan - Ulul Asmy; Asrianto Asrianto; Hardianti Hardianti; Dwi Astuti; Arnianti Arnianti; Mahyudin Mahyudin (Journal on Education, 2025)
Enteral nutrition is a therapy of providing nutrition through the digestive tract using a special tube (feeding tube). The method of administration can be through the nose-stomach (nasogastric tube) or nose-intestine (nasoduodenal tube or nasojejunal route). Enteral nutrition can also be done by bolus or infusion through an enteral infusion pump. The purpose of this study was to determine the effectiveness of enteral nutrition. The methods used were intermittent feeding and gravity drip on the volume of gastric residue in critical patients. The results showed that the provision of enteral nutrition using the intermittent feeding method was proven to be more effective so that the provision of enteral nutrition using the intermittent feeding method can be an option in providing enteral nutrition to critical patients. The conclusion is that the intermittent feeding method helps meet the nutritional needs of critical patients in the ICU.